Composición florística y estructura de la vegetación leñosa en áreas de restauración pasiva del bosque seco de la reserva natural Laipuna, cantón Macará, provincia de Loja - Ramón Naula, Karina Anabel (2024)
Tropical dry forests are ecosystems threatened by agricultural and livestock activities, whose land use dynamics have caused an agricultural and livestock mosaic, intensified in abandoned areas; the latter by the action of natural regeneration processes have formed secondary forests, whose dynamics need to be studied and understood. For this purpose, we proposed to characterize the floristic composition and determine the tree structure of the tropical dry forest in passive restoration processes. The present study was conducted in an area of passive restoration of approximately 20 years in the dry forest in the Laipuna Nature Reserve; four plots of 50 × 50 m were inventoried and tree individuals ≤ 5 cm were recorded, structural parameters such as density, relative density, relative dominance, frequency and importance value index were calculated. The basal area per diameter class was calculated for the forest structure. For the structural profiles, a 50 m x 10 m transect was drawn, where the location of the trees was recorded in X and Y coordinates, height, crown distance and tree shape. The results obtained show 35 species within 31 genera and 17 families with a total of 835 individuals, the most representative families being Fabaceae, Nygtaginaceae, Asteraceae. The most representative species for having the largest number of individuals and being ecologically more important in this stage of passive restoration were Vachellia macracantha, Ipomoea wolcottiana, Erythrina velutina, Leucaena trichodes, Handroanthus chrysanthus, presenting a medium diversity according to the Shannon Index. The structure has the highest number of individuals in the lower diameter classes, the basal area is concentrated in the first three diameter classes, representing 76 % of the total basal area. The results indicate that the restoration area is in a state of early to intermediate succession